Putative role for interleukin-7 in the maintenance of the recirculating naive CD4+ T-cell pool. - Webb, L; Foxwell, B; Feldmann, M (1999)
The capacity of the immune system to respond efficiently to new antigens depends upon a continuous source of naive CD4+ T cells. Such cells exit from the thymus and join the recirculated T-cell pool. Factors present at the sites of naive CD4+ T-cell circulation must be responsible for their survival, since upon removal from their host, naive CD4+ T cells die. However, such factors remain unknown. The presence of the cytokine interleukin-7 (IL-7) in secondary lymphoid organs and the continuous expression of its receptor on naive CD4+ T cells prompted us to examine the possibility that IL-7 might be a survival factor for naive CD4+ T cells. Using naive CD4+ T cells isolated from cord blood we show that IL-7, but not IL-2, can maintain naive CD4+ T-cell viability in vitro for at least 15 days. In addition, we find that IL-7 can induce modest proliferation of naive CD4+ T cells without affecting either their cell surface phenotype or their ability to respond to antigenic stimulation. We also find that after anti-CD3 stimulation, naive CD4+ T cells lose that ability to respond to IL-7. However, if cells are primed with IL-7 prior to antigenic stimulation, their proliferative responses are enhanced. Together, these data suggest a novel and important role for IL-7 in the maintenance and maturation of naive CD4+ T cells, ensuring that they can respond maximally when they first meet antigen in secondary lymphoid tissue.